Цельность разговорного тетста в свете категориальных сопоставлении - БОРИСОВА, ИРИНА Н. (Stylistyka, 2021)
The article deals with а textual manifestation of integrity of colloquial dialogue. It is based on а textual concept of colloquial interaction. Correlation of pragmatic categories (subject theme (topic), extralinguistic situation, strategy and communicative coordination of speech behavior, text completion) with text integrity makes possiЫe to ascertain textual, structural, semantic and psycholinguistic essence of colloquial dialogue integrity. Orginal records of live city speech are used as а basic reference material.